STRATEGIC EDUCATIONAL LEADERSHIP AND ITS IMPACT ON QUALITY ASSURANCE IN HIGHER EDUCATION INSTITUTIONS - Isakulova Baxtigul Khojamovna (Bright Mind Publishing, 2025)
In the rapidly evolving landscape of higher education, quality assurance (QA) has become a fundamental pillar for ensuring academic excellence, institutional credibility, and global competitiveness. This article examines the role of strategic educational leadership in shaping and enhancing QA processes within higher education institutions (HEIs). It argues that leadership which is vision-driven, participatory, and adaptive to change significantly influences institutional culture, stakeholder engagement, and policy development. By integrating internal and external QA mechanisms, strategic leaders can promote continuous improvement, foster academic integrity, and align institutional missions with national and international standards. However, challenges such as limited resources, resistance to change, and overreliance on global ranking systems often hinder effective QA implementation. Drawing on best practices, this study emphasizes transparent evaluation, participatory governance, technological integration, and sustainable leadership development as key strategies for success. The article concludes that effective strategic educational leadership is not only managerial but transformative, positioning QA as a dynamic process that strengthens institutional resilience and advances higher education quality in the 21st century.
Keywords: Strategic educational leadership; quality assurance; higher education institutions; academic excellence; institutional governance; transformational leadership; policy development; organizational culture; stakeholder engagement; continuous improvement; accreditation; higher education management.